(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
This article presents the experience of the team responsible for implementing a university extension program with regard to the use of Instagram as a tool for communication and health education for the community, as well as information about its reach and the topics addressed on this social network. This experience is based on the principle that virtual platforms are increasingly recognized and utilized for general information and training in public health and, therefore, should be incorporated into academic extension proposals. The program—Brincando de Respirar—encompasses six projects described by evaluation, guidance, and pediatric respiratory physiotherapy intervention. It involves children and their caregivers, as well as other professionals, to ensure success in the prevention, promotion, and recovery of respiratory health within the specified population. The use of Instagram by the program team, through systematically organized educational content and posts on the social network, has expanded the scope of the involved projects, as it provides the community with unrestricted access to activities and knowledge related to pediatric respiratory physiotherapy.